Assessment of sheep oocyte quality for in vitro maturation - RANGASAMY, S; KULASEKAR, K; BALASUBRAMANIAN, S; DHINAKAR RAJ, G (The Indian Journal of Animal Reproduction, 2023)
Sheep ovaries were collected from slaughter house and transported to the laboratory within 30 min. Atotal of 2117 oocytes were retrieved using slicing technique with a rec~very rate of 4.9 l oocytes per ovary.Among the collected oocytes 33.87 (717), 32.73 (693) and 33.40 (707) per cent of oocytes were graded as A, Band C, respectively. The mean maturation percentage of A, Band C grade oocytes in the present study was 95.48± 0.63, 89.14 ± 1.17 and 77.94 ± 1.12, respectively. The maturation rate of A grade oocytes were significantly(
Keywords: Sheep; Oocytes; In vitro maturation